2018
DOI: 10.1016/j.jnutbio.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Copper supplementation reverses dietary iron overload-induced pathologies in mice

Abstract: Dietary iron overload in rodents impairs growth and causes cardiac hypertrophy, serum and tissue copper depletion, depression of serum ceruloplasmin (Cp) activity and anemia. Notably, increasing dietary copper content to ~25-fold above requirements prevents the development of these physiological perturbations. Whether copper supplementation can reverse these high-iron-related abnormalities has, however, not been established. The current investigation was thus undertaken to test the hypothesis that supplemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Copper, an essential redox-active trace element, which is essential for most aerobic organisms (Tapiero et al, 2003;Solomon et al, 2014). Simultaneously, copper functions as a co-factor of various proteins and enzymes, including cytochrome C, superoxide dismutase, tyrosinase, ascorbate oxidase, lysyl oxidase, and amine oxidase, exhibiting diverse fundamental cellular functions in normal physiology, including energy generation, iron acquisition, oxygen transportation, cellular metabolism, peptide hormone maturation, blood clotting, neurotransmitter biosynthesis, and intracellular signal transduction (Huffman and O'Halloran, 2001;Hamza and Gitlin, 2002;Kim et al, 2008;Turski et al, 2012;Grubman and White, 2014;Wang et al, 2018;Miller et al, 2019). Generally, copper is able to exist in two oxidation states in the body of mammalians: Cu + and Cu 2+ (Lin and Kosman, 1990;Pushie et al, 2007;Solomon et al, 2014).…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…Copper, an essential redox-active trace element, which is essential for most aerobic organisms (Tapiero et al, 2003;Solomon et al, 2014). Simultaneously, copper functions as a co-factor of various proteins and enzymes, including cytochrome C, superoxide dismutase, tyrosinase, ascorbate oxidase, lysyl oxidase, and amine oxidase, exhibiting diverse fundamental cellular functions in normal physiology, including energy generation, iron acquisition, oxygen transportation, cellular metabolism, peptide hormone maturation, blood clotting, neurotransmitter biosynthesis, and intracellular signal transduction (Huffman and O'Halloran, 2001;Hamza and Gitlin, 2002;Kim et al, 2008;Turski et al, 2012;Grubman and White, 2014;Wang et al, 2018;Miller et al, 2019). Generally, copper is able to exist in two oxidation states in the body of mammalians: Cu + and Cu 2+ (Lin and Kosman, 1990;Pushie et al, 2007;Solomon et al, 2014).…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…Here, our intent was to test the hypothesis that high intake of dietary iron in previously ID rat dams would have pathological outcomes for suckling pups. This investigation builds logically on our previous work in rats and mice demonstrating that iron intake at levels ≈5-fold above requirements causes copper depletion and associated pathological outcomes [ 13 , 14 , 15 , 16 ]. Although we are investigating the effect of high enteral iron on copper absorption, it is also important to consider possible influences of high iron on the absorption of other minerals (e.g., zinc).…”
Section: Discussionmentioning
confidence: 71%
“…Additional recent investigations supported these postulates, as increases in dietary iron resulted in copper deficiency-related pathological outcomes in adolescent rats [ 13 , 14 ] and mice [ 15 ]. Copper supplementation of mice consuming a high-iron diet prevented the development of these pathologies, proving that they related specifically to copper depletion [ 16 ]. Collectively, these investigations suggested that high iron consumption increases the dietary requirement for copper, supporting the previous assertion that iron supplements should contain extra copper [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies in acute‐on‐chronic liver failure have assessed whether changes in iron homeostasis and neutrophils (whose maturation and function depend on copper) is related to copper deficiency . This may be important, because if copper deficiency indeed exists, it becomes a potential target of intervention in which copper supplementation might (1) improve pathological consequences of iron overload and (2) restore immune cell function as it did in experimental animals …”
Section: Discussionmentioning
confidence: 99%